PENGARUH PEMBERIAN PRODUK BERBAHAN KACANG KEDELAI (Glycine max) TERHADAP PENURUNAN TEKANAN DARAH - Gina Edya Triandini; Suhaema Suhaema; Retno Wahyuningsih; Fifi Luthfiyah (Poltekkes Kemenkes Mataram, 2021)
Background : The prevalence of hypertension in West Nusa Tenggara in 2013 was 24.3%, this figure increased in 2018 to 27.8%. Treatment of hypertension can be done in two ways, namely, pharmacology and non pharmacology. Non-pharmacological treatment can be done with the Dietary Approaches to Stop Hypertension (DASH) diet and consuming functional foods, one of which is soybeans. Soybeans contain isoflavones and the amino acid tryptophan which can reduce the risk of cardiovascular disease, one of which is hypertension. Objectives : Objectives in this literature study is to examine the effect of giving soybean based products on reducing blood pressure from various literature sources.Methods : The literature search in this literature study uses three databases, namely Google Scholar, Microsoft Academia, and Garuda Portal. The keywords used in the literature search were